Bevacizumab to Treat Cholangiopathy in Hereditary Hemorrhagic Telangiectasia: Be Cautious: A Case Report. Issue 46 (November 2015) - Maestraggi, Quentin; Bouattour, Mohamed; Toquet, Ségolène; Jaussaud, Roland; Kianmanesh, Reza; Durand, François; Servettaz, Amélie
Abstract : Abstract: Hereditary hemorrhagic telangiectasia (HHT) is an inherited vascular dysplasia characterized by mucocutaneous telangiectasia and visceral arteriovenous malformations. Hepatic involvement with vascular malformations may lead to portal hypertension, biliary ischemia, and high-output cardiac failure. There is no curative treatment for the disease. Liver transplantation is indicated for life-threatening complications, but it carries significant risk due to surgery and immunosuppressive treatment. Some case reports or small open studies suggest that bevacizumab, a recombinant humanized anti-VEGF monoclonal antibody, should be efficient in limiting bleeding and in reducing liver disease in HHT. We report a case of a 63-year-old woman with HHT presenting with ischemic cholangiopathy. Liver transplant was indicated, but given a previous encouraging report showing a regression of biliary disease with bevacizumab in 3 patients with HHT this drug was proposed. No significant efficacy but a severe adverse effect was observed after 3 months: bilateral pulmonary embolisms, thrombosis in the right atrial cavity, and thrombosis of the right hepatic vein were evidenced. Bevacizumab was stopped; anticoagulant started. Four months later, the patient received a transplanted liver. She feels well 1 year later. This case report intends to provide the information for clinicians to consider the use of bevacizumab in HHT. Whereas several uncontrolled series and case reports have suggested the efficacy of this drug in reducing bleeding and liver disease, no severe side effects were mentioned to date. For the first time in HHT we report a life-threatening side effect of this drug and no efficacy. Moreover, systemic thrombosis, the observed complication, may preclude transplantation. To date, caution seems still indispensable when considering the use of bevacizumab in HHT.